EMPLOYMENT GENERATION THROUGH STANDARD HOTEL INDUSTRY BUSINESS: MYTHS AND REALITIES!! - Dayanandan, Dr. (IJRDO - Journal of Business Management, 2016)
Role of the modern service sector like standard hotel industries is an alternative stimulant tosocio-economic development, poverty reduction and job creation and its increasing demandand supply gap. However, due to different constraints and factors, this may not be achievedthe socio-economic advantages of the society through employment as expected from standardhotels investment in the study area. Hence the main objective of this paper is to assess therole of standard hotel industry business in employment gemeration. The study is based onboth quantitative and qualitative in nature with the help of primary and secondary data.Primary data was collected through survey questionnaire, administered to employees andmanagement members of sample standard hotels, selected by systematic sampling technique.Secondary data was obtained through review of literatures, regional investment data baseand the regional culture and tourism bureau reports. Descriptive analysis was employed andargumentative explanations and narrations are provided from qualitative information.The findings indicate that socio-economic benefits of the society through employmentgeneration from the standard hotel business are inefficient and instability, which is in favorof the employers rather than employees. Inefficient employment characteristics are absenceof transparency and accessibility, selectiveness and low qualification. Attributes foremployment instability are poor working conditions and unsuitable environment, absence ofmotivation, incentives and unequal treatment between management members and workersthat the management members benefit better than workers because a significant number ofworkers cannot afford for personal savings, upgrade education and personal problems. Asthe results indicate, standard hotel business failed to achieve the expected socio-economicgains through employment. Further both both demand and supply side constraints areresponsible for identified inefficiencies. Therefore, improving the existing operation withrecommendable means of intervention is appropriate to address the problems.